IMPOSITION OF ANTIDUMPING DUTY (BAMD) TOWARDS CHINA’S COLD ROLLED COIL/ SHEET (CRC/S) PRODUCTS - Pratiwi, Lila (UI Scholars Hub, 2013)
Steel industry is a strategic sector in the economy of a country. Steel industry in Indonesia has not been able to fulfill their domestic demand that is still necessary to import steel product. However, many of these imported products are sold at dumping prices, especially those from china giving rise to unfair trade. One of trade remedy measures as a result of unfair trade remedies can recover trough the imposition of antidumping duty. In 2013, Indonesia imposes antidumping duty for Cold Rolled Coil/ Sheet (CRC/S) from China and other countries. Imposition of antidumping duty will be analyzed descriptively with the antidumping agreement conformity. While, it cannot be denied that political factors also determine imposition of antidumping duty. It is need to use analytical theory of justice in order to enforce fair-trade